2012
DOI: 10.1111/j.1365-2265.2012.04506.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between body mass index and clinico‐pathological characteristics of papillary thyroid cancer

Abstract: Higher BMI was strongly associated with larger tumour size, extrathyroidal invasion and advanced TNM stage of PTCs. However, there was no difference in recurrence rate among BMI groups. This study suggests that excess weight is associated with aggressive features of PTCs. Further studies with long-term follow-up are needed to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
7
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 33 publications
8
83
7
4
Order By: Relevance
“…Future studies should address interactions between chemotherapy and known thyroid cancer risk factors, including radiation, 14,24 family history, 47 and obesity. 48 The high prevalence of increased body mass index as a component of metabolic syndrome is well established in survivors of TC 49 and may serve as an additional explanation for our observations. Teratoma may undergo malignant transformation to any histologic subtype, 16 with soft tissue sarcoma being the most frequent (63%).…”
Section: Solid Tumors After Testicular Nonseminomamentioning
confidence: 59%
“…Future studies should address interactions between chemotherapy and known thyroid cancer risk factors, including radiation, 14,24 family history, 47 and obesity. 48 The high prevalence of increased body mass index as a component of metabolic syndrome is well established in survivors of TC 49 and may serve as an additional explanation for our observations. Teratoma may undergo malignant transformation to any histologic subtype, 16 with soft tissue sarcoma being the most frequent (63%).…”
Section: Solid Tumors After Testicular Nonseminomamentioning
confidence: 59%
“…These results suggest an important role of excess total (as opposed to central) adiposity across the lifespan on thyroid cancer incidence. Prospective studies that directly evaluate pre-diagnostic levels of biomarkers of insulin resistance, inflammation, estrogen, and other metabolic disturbances related to total adiposity may provide some insight regarding possible underlying mechanisms (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Kim and colleagues showed that obesity was not only associated with an increased risk of thyroid cancers, but could also exert an influence on tumor presentation. They reported that a 5-kg/m 2 increase in the BMI was associated with PTCs O1 cm (ORZ1.31; P!0.001), microscopic extrathyroidal invasion (ORZ 1.23; PZ0.006), and advanced tumor/node/metastases (TNM) stage (ORZ1.30; PZ0.003) (Kim et al 2013a). Some other authors have been reinforcing the data on the relationship between obesity and thyroid cancer, and the most recent studies have focussed on the possible links for this association, such as diabetes and/or IR (Shih et al 2012, Tseng 2013, cytokines (Cheng et al 2012, Di Cristofano 2013, diet (Kim et al 2013b), anthropometric factors (Kim et al 2013c), and even genetic variants that might affect susceptibility to thyroid cancers (Kitahara et al 2012a,b).…”
Section: Association Between Overweight and Thyroid Cancer: Observatimentioning
confidence: 99%